Investigating the Onset of Strain Localization Within Anisotropic Shale Using Digital Volume Correlation of Time‐Resolved X‐Ray Microtomography Images. Issue 9 (17th September 2018) - McBeck, Jessica; Kobchenko, Maya; Hall, Stephen A.; Tudisco, Erika; Cordonnier, Benoit; Meakin, Paul; Renard, François
Abstract: Digital volume correlation analysis of time‐resolved X‐ray microtomography scans acquired during in situ triaxial compression of Green River shale cores provided time series of 3‐D incremental strain fields that elucidated evolving deformation processes by quantifying microscopic strain localization. With these data, we investigated the impact of mechanical anisotropy on microscopic strain localization culminating in macroscopic shear failure. We conducted triaxial compression experiments with the maximum compressive stress, σ 1, aligned perpendicular and parallel to lamination planes in order to investigate end‐member stress states that arise within sedimentary basins. When the preexisting laminations were perpendicular to σ 1, a lamination‐parallel region with high axial compaction developed within the macroscopically linear deformation phase of the experiment and then thickened with increasing applied differential stress. Scanning electron microscopy images indicate that this axial compaction occurred within a lower density lamination and that more axial compaction occurred within the center of the core than near its sides. Boundary element method simulations suggest that this compacting volume promoted shear fracture development within the upper portion of the shale. When the laminations were parallel to σ 1, lamination‐parallel dilation bands formed, thickened, and intensified in dilation. Population densities of the distributions of incremental shear strain, radial dilation, and axial contraction calculated by digital volume correlation analysis enabled quantification of the evolving overall impact of, and interplay between, these various deformation modes. Key Points: Time‐resolved in situ X‐ray tomography imaging captured the path to macroscopic shear failure within shale Lamination‐parallel zones of high incremental axial contraction and radial dilation developed prior to macroscopic failure Digital volume correlation and numerical modeling results suggest that axial compaction promoted shear strain localization